Missing Joseph - George, Elizabeth, 1949-. (Bantam, 1993)
When Deborah St James hears of the unexpected death of Reverend Sage, her sadness has a very personal tinge. For their paths had crossed some months earlier at a particularly vulnerable time for Deborah, and she had found herself confessing her intimate anguish to this sympathetic stranger. When she realizes that his death is far from accidental, Deborah, with her husband, Simon, enlists the help of Inspector Lynley, and the trio embarks upon an investigation that hinges upon the overriding - and ulimately destructive - power of parental love.